Fractional exhaled nitric oxide for the management of asthma in adults: a systematic review. Issue 3 (4th February 2016) - Essat, Munira; Harnan, Sue; Gomersall, Tim; Tappenden, Paul; Wong, Ruth; Pavord, Ian; Lawson, Rod; Everard, Mark L.
The aim of this review was to evaluate the clinical effectiveness of fractional exhaled nitric oxide ( F eNO ) measured in a clinical setting for the management of asthma in adults. 13 electronic databases were searched and studies were selected against predefined inclusion criteria. Quality assessment was conducted using QUADAS-2. Class effect meta-analyses were performed. Six studies were included. Despite high levels of heterogeneity in multiple study characteristics, exploratory class effect meta-analyses were conducted. Four studies reported a wider definition of exacerbation rates (major or severe exacerbation) with a pooled rate ratio of 0.80 (95% CI 0.63–1.02). Two studies reported rates of severe exacerbations (requiring oral corticosteroid use) with a pooled rate ratio of 0.89 (95% CI 0.43–1.72). Inhaled corticosteroid use was reported by four studies, with a pooled standardised mean difference of −0.24 (95% CI −0.56–0.07). No statistically significant differences for health-related quality of life or asthma control were found. F eNO guided management showed no statistically significant benefit in terms of severe exacerbations or inhaled corticosteroid use, but showed a statistically significant reduction in exacerbations of any severity. However, further research is warranted to clearly define which management protocols (including cut-off points) offer best efficacy and which patient groups would benefit the most. F eNO testing for adult asthma management may confer clinical benefit, but research is needed to establish its role http://ow.ly/WGWkx